Longitudinal SS-OCT choroidal imaging following thrombosis of the superior ophthalmic vein - Mengxi Shen; Prashanth G. Iyer; Hao Zhou; Yuxuan Cheng; Jeremy Liu; Omer Trivizki; Ruikang K. Wang; Giovanni Gregori; Philip J. Rosenfeld (American Journal of Ophthalmology Case Reports)
Purpose: To report longitudinal changes in choroidal thickness and the choroidal vasculature using SS-OCT imaging in a patient with superior ophthalmic vein thrombosis (SOVT). Observations: In a 93-year-old woman with a left-sided SOVT, the choroid in the left eye was thickened and the choroidal vessels were dilated both superiorly and inferiorly, with greater changes evident in the inferotemporal region of the choroid. After the superior ophthalmic vein was decompressed, a decrease in the choroidal thickness and choroidal vessel dilatation was observed both superiorly and inferiorly. Conclusions and importance: In an eye with thrombosis of the superior ophthalmic vein, longitudinal SS-OCT choroidal imaging showed a greater increase in choroidal thickness and choroidal vessel dilation away from the obstructed quadrant, which improved after treatment. These observations associated with outflow obstruction may be applicable to other choroidal diseases characterized by venous overload.